Sustainable polymers and sisal fibers based green composites: A detailed characterization and analysis - Karri Santosh Kumar; Sandeep Gairola; Inderdeep Singh (eXPRESS Polymer Letters)
In the global pursuit of using sustainable constituents for developing composite materials, the current investigation has paid particular attention to the most promising biopolymers, such as poly(lactic acid) (PLA) and bio-based poly(butylene succinate) (bio PBS). The research endeavor emphasizes a comparative assessment of short sisal fiber (SF) reinforced (10,20, and 30 wt%) PLA and bio PBS biocomposites. The analysis and discussion have been reported for the thermal, mechanical,crystallinity, and dynamic mechanical behavior of developed composite materials. Based on mechanical properties, the optimal fiber loading for SF/PLA and SF/bio PBS biocomposites was 20 and 30 wt%, respectively. The developed composites have shown a considerable improvement in crystallinity of 17.88 and 41.13% at 20 and 30 wt% of fiber loading in SF/PLA and SF/bio PBS, respectively. The maximum storage modulus values of 14.23 GPa (20SF/PLA) and 11.74 GPa (30SF/bio PBS) were observed. The loss modulus of the SF/PLA and SF/bio PBS composites was around 74 and 89% higher than the loss modulus of the PLA and the bio PBS matrix, respectively. Overall, composites fabricated with bio PBS (SF/bio PBS) have shown better crystallinity, thermal stability, and ease of processing than SF/PLA composites.